2013
DOI: 10.1161/circoutcomes.113.000375
|View full text |Cite
|
Sign up to set email alerts
|

The YOU CALL–WE CALL Randomized Clinical Trial

Abstract: Background-Comparison of a multimodal intervention WE CALL (study initiated phone support/information provision) versus a passive intervention YOU CALL (participant can contact a resource person) in individuals with first mild stroke. Methods and Results-This study is a single-blinded randomized clinical trial. Primary outcome includes unplanned use of health services (participant diaries) for adverse events and quality of life (Euroquol-5D, Quality of Life Index). Secondary outcomes include planned use of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Four studies required conversion of the data to mean and standard deviation; one each reported median and interquartile ranges 27 and median and range values, 33 and two reported mean and CI values 28,42 The ages of the stroke survivors ranged from 30 to 91 years. The length of the intervention ranged from 4 weeks 44 to 12 months 35,37 , with duration of 4 weeks 44 to 6 months 39,41,43 in most of the studies (22/24). Individual study details are included in Table 1 and present seven support service studies, eleven exercise studies, three mixed studies (support service and exercise) and three other studies which did not involve exercise or support service.…”
Section: Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies required conversion of the data to mean and standard deviation; one each reported median and interquartile ranges 27 and median and range values, 33 and two reported mean and CI values 28,42 The ages of the stroke survivors ranged from 30 to 91 years. The length of the intervention ranged from 4 weeks 44 to 12 months 35,37 , with duration of 4 weeks 44 to 6 months 39,41,43 in most of the studies (22/24). Individual study details are included in Table 1 and present seven support service studies, eleven exercise studies, three mixed studies (support service and exercise) and three other studies which did not involve exercise or support service.…”
Section: Included Studiesmentioning
confidence: 99%
“…Studies utilizing support services included telephone calls 25,41 , home visits 35,39 , educational courses 31,34 , mailed educational information 39 and group discussions. 36 Studies utilizing support services as an intervention or in combination with other interventions 25,27,31,[33][34][35][36][37]39,41 had a frequency of at least one session per month for eight weeks.…”
Section: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations